Ethnomathematics Exploration of Carvings in Asei Community Houses as a Source of School Mathematics Learning - Waralangi, Aprilia Dian; Kho, Ronaldo; Tandililing, Pitriana; Sirampun, Elsi; Ruamba, Marthinus Y (JUPE : Jurnal Pendidikan Mandala, 2025)
The Asei people are known for their distinctive local cultural heritage, particularly in the form of carvings that decorate their house walls. These carvings serve not only as symbols of cultural and social identity but also contain visual structures rich in mathematical concepts. This study aims to explore and describe the mathematical elements found in the carvings of houses in the Asei community, located in East Sentani District, Jayapura Regency, Papua, as well as to examine their potential as a source for school mathematics learning. This research employs a qualitative approach using ethnographic methods. Data were collected through direct observation, in-depth interviews with two informants knowledgeable about the meanings of the carvings, and visual documentation. The collected data were analyzed through a continuous interactive process of data reduction, data presentation, and conclusion drawing. The results reveal that the carvings on Asei houses encompass various mathematical elements, including reflection, symmetry, rotation, dilation, as well as geometric shapes such as circles, triangles, parallelograms, trapezoids, parallel lines, obtuse angles, and acute angles. These elements are found within seven main carving motifs, namely kino, heuw, iuwga, me khela-khela, fouw, khaley, and kheika.